Growth Analysis of Mahogany Seeds Using Android Based Seed Measurement Applications - Kholil, Muhammad kholil asyari; Hartanti, Dyah Ayu Sri; Widya, Moh Anshori Aris (NEWTON: Networking and Information Technology, 2023)
This mahogany seed measurement application is one of the systems used to simplify the analysis process for mahogany seeds. This application measurement is used to determine the development of mahogany seedlings when it's time to move. This research on making a simple application for measuring mahogany seeds which is not widely known by the wider community which has the potential to become one of the applications that are needed by Mahogany Farmers. This simple application receives an input in the form of data, then it is determined for various reasons so that these seeds are feasible to be moved to a more adequate place. The criteria for relocating were the small number of dead mahogany seedlings with a certain age, the height of the mahogany seeds and the good condition of the mahogany seeds. This research was conducted to make it easier for mahogany seed farmers to analyze the development or growth of mahogany seedlings and to make it more practical to use.